Anastomotic Stricture in End-to-End Anastomosis—Risk Factors in a Series of 261 Patients with Esophageal Atresia - Koivusalo, Antti; Mutanen, Annika; Suominen, Janne; Pakarinen, Mikko (European Journal of Pediatric Surgery, 2021)
Aim To assess the risk factors for anastomotic stricture (AS) in end-to-end anastomosis (EEA) in patients with esophageal atresia (EA).Methods With ethical consent, hospital records of 341 EA patients from 1980 to 2020 were reviewed. Patients with less than 3 months survival (n = 30) with Gross type E EA (n = 24) and with primary reconstruction (n = 21) were excluded. Outcome measures were revisional surgery for anastomotic stricture (RSAS) and number of dilatations required for anastomotic patency without RSAS. The factors that were tested for risk of RSAS or dilatations were distal tracheoesophageal fistula (TEF) at the carina in C-type EA (congenital TEF [CTEF]), type A/B EA, antireflux surgery (ARS), anastomotic leakage, recurrent TEF, and Spitz group and congenital heart disease.Main Results A total of 266 patients, Gross type A (n = 17), B (n = 3), C (n = 237), or D (n = 9) underwent EEA (early n = 240, delayed n = 26). Early anastomotic breakdown required secondary reconstruction in five patients. Of the remaining 261 patients, 17 (6.1%) had RSAS, whereas 244 patients with intact end to end required a median of five (interquartile range: 2–8) dilatations for anastomotic patency. Main risk factors for RSAS or (> 8) dilatations were CTEF, type A/B, ARS, and anastomotic leakage that increased the risk of RSAS or dilatations from 4.6- to 11-fold.Conclusion The risk of severe AS is associated with long-gap EA, significant gastroesophageal reflux, and anastomotic leakage.
Keywords: esophageal atresia; anastomotic stricture; end-to-end repair